Allergen immunotherapy in Italy: How, when, and why—A real-world study conducted through a patient association - Giovanni Paoletti, MD; Emanuele Nappi, MD; Maria Chiara Bragato, MD; Paola Valli, MD; Mattia Giovannini, MD; Domenico Gargano, MD; Luca Pecoraro, MD; Deborah Diso, MSc; Simona Barbaglia, MSc; Giorgio Walter Canonica, MD; Enrico Heffler, MD, PhD (World Allergy Organization Journal)
Background: Allergen immunotherapy (AIT) is the only treatment that modifies the natural course of allergies. However, AIT is only used in some eligible patients, is frequently underused, and only a few studies investigated this aspects. Understanding AIT utilization patterns might disclose information about why it is underused, thus providing valuable insights on how to broaden the positive impact it can have on the population. Methods: A questionnaire aiming to assess the trends of the use of AIT in Italy, patient health literacy on AIT, and the impact of respiratory allergies and AIT on patients' lives was submitted to patients affiliated with Respiriamo Insieme APS patient's association during the period between May and October 2023. Results: Nine hundred forty-four patients completed the questionnaire. Most patients reported to be affected by allergic rhinitis (81.1%), allergic asthma (45.4%), and/or allergic conjunctivitis (41.2%), and many of them presenting a combination of these diseases. Only 53.8% knew about AIT's existence, and AIT was proposed to only 33.1% of the 858 patients affected by allergic rhinitis and/or allergic asthma, of which 29.2% decided not to initiate the therapy. Common reasons for AIT refusal were related to indecisiveness (26.5%), costs (22.9%), and skepticism (19.3%). Among the remaining 70.8% who accepted to start AIT, 21.4% discontinued the treatment beforehand, on average 18.26 months from initiation. There was a high heterogeneity in the suggested duration of AIT, with 20.4% of patients receiving indications to continue AIT for less than 3 years. AIT positively impacted patients' lives as most patients who completed AIT found it effective and safe, and experienced a significant reduction in the workdays/schooldays lost due to disease exacerbations. Conclusions: The outcomes of this research pointed out a lot of misinformation surrounding AIT, calling for improvements in awareness and information on its efficacy and safety. Also, we noted a significant reduction in work/school days lost in patients who completed AIT and a good patient-reported safety and efficacy profile. We advocate for better economic accessibility through national-level standardization in treatment refundability. Notably, the collaboration with the patient association was crucial, and it would have been challenging to conduct this research otherwise.